The Improved Determination of the Source Boundaries for Earthquakes of M 7 of the Seismic Prediction for the Kurile-Kamchatka Arc - Fedotov S.A.; Chernyshev S.D.; Chernysheva G.V. (My University, 1982)
Abstract. Based on a great amount of data on seismicity of the Kurile Islands and Kamchatka which have been accumulated since 1965, a detailed study has been made of the seismic regime of the regions of M . 1\ earthquakes in the Southern Kurile Islands, Kamchatka and near Northeastern Japan in the period 1952-1978. A rule has been deduced for the construction of source boundaries of M 7f earthquakes that permits more accurate and reliable identification of locations of likely catastrophic earthquakes. The mean line between seismic activity isolines Alo = 10 and released seismic energy D = 1 for the first-year aftershocks is taken as a source boundary. In addition, in doubtful cases, the position of a smooth contour of the area of M 3* 6 aftershocks, which occurred within the first year after the main shock, was taken into account. The new materiai was used to test cycles of seismic activity Al0 (t) and seismic energy release D (t) for M. \ earthquakes. Cycle Alo (t) did not change substantially in comparison to the former constructions; the minimum in cycle D (t) in the stable regime stage disappeared and the root-mean-square deviation of this value decreased. A test was made of prediction for 1971-1975 which proved to be reasonably successful. A prediction for 1976-1980 was refined. A preliminary prediction for 1981-1985 is presented.
Keywords: 37.31.19 Сейсмология